Estimation of ankle joint parameters in typically developed adults using functional calibration methods - Salami, Firooz; Wolf, Sebastian Immanuel; Simon, Jan; Leboucher, Julien; Heitzmann, Daniel; Dreher, Thomas; Götze, Marco (Gait & posture, 2020)
Background - Despite of many attempts to determine or correct hip and knee joint parameters via non-invasive techniques such as regression or functional methods, in conventional gait models the position of the ankle joint center still is assumed at the center point between malleoli. - Research question - The aim of this study was to estimate the ankle joint parameters using a functional approach. - Methods - To this aim, we used data of 23 typically developed adults performing two different calibration motions. Subsequently, we applied functional approaches to determine the functional joint center and axis. - Results - The results show significant differences for ankle joint parameters in all directions for both calibration motions applied with respect to the malleoli line. Most prominently, we find a shift of the ankle joint center of 7 % of the foot length anteriorly to the malleoli mid-point when applying functional calibration. - Conclusion - These significant alterations of the ankle joint center and axis indicate the importance of accurate determination of ankle joint parameters and consequently their influence on the clinical outcome.
Gesehen am 09.04.2020